NETosis and the Immune System in COVID-19: Mechanisms and Potential Treatments - Gillot, Constant; Favresse, Julien; Mullier, François; Lecompte, Thomas; Dogné, Jean-Michel; Douxfils, Jonathan (Frontiers in Pharmacology, 2021)
NETosis is a form of neutrophil death leading to the release of extracellular chromatin and the assembling of proteins, including antiviral proteins, traps primed by an initial pathogenic stimulus. Under certain specific conditions, neutrophils can exhibit a double-edged activity. This event has been inplicated in COVID-19 among other conditions. Neutrophil extracellular traps (NETs) are involved in the pathogenesis of COVID-19 by promoting a pro-inflammatory and a pro-coagulant state leading to multiorgan failure. This particular form of host defense promoted by neutrophils is closely related to the well-known cytokine storm observed in severe COVID-19 patients. These two elements therefore represent possible targets for treatment of severe SARS-CoV-2 infections.